Birds of the Rawa Aopa Watumohai National Park, South-East Sulawesi - J C Wardill; P S Fox; D J Hoare; W Marthy; K Anggraini (Indonesian Ornithologists’ Union, 1998)
The Rawa Aopa Watumohai National Park was visited between 9 September and 9 November 1995 and surveys conducted from a range of localities within the park. This constitutes the first study of the avi fauna of this large protected area. A total of 157 different species were recorded (155 to species level) including Mycteria cimerea, Macrocephalon maleo, Cacatua sulphurea and Zoosterops consobrinorum. An annotated list of selected species is presented and a full species list appears as an. appendix.